Analisis Perkembangan Permukiman Kecamatan Paron Kabupaten Ngawi Tahun 2002-2018 - GRIZKA LUTHFIAH PRAMESWARI (Universitas Sebelas Maret (UNS), 2023)
This study aims to: (1) Knowing the development of settlements. (2) The pattern of distribution of settlements. (3) Factors influencing the development of settlements in Paron District, Ngawi Regency in 2002-2018. The research was conducted in Paron District, Ngawi Regency. The population of this research is KK.The sample that will be used in this research is cluster sampling based on the number of additional residential lands and the increase in the number of heads of families.There are 3 data analysis techniques based on the formulation of the problem, namely: (1) Settlement development using spatial analysis. (2) The pattern of distribution of settlements using the nearest neighbor analysis technique according to Bintarto (1991: 74). (3) Factors influencing the development of settlements from data processing after collecting data through various sources, which will then be classified. According to Yunus (1987: 73) there are nineteen significant reasons for the attractiveness of the population to move. The results of this study: (1) The area of settlements/buildings located in the research area in 2002 was 1,520.1 Ha, in 2010 the area was 1,809.9 Ha, resulting in an increase in the use of residential land as much as 289.8 Ha. In 2010 the settlement area was 1,809.9 Ha, in 2018 the total settlement area was 2,175.36 Ha, the changes that occurred were 365.46 Ha. (2) The pattern of distribution of settlements in Paron District has a result of Ta = 0.00016320772, it is concluded that it is close to a clustered pattern with T = 0-1. (3) The most dominant factor among the 19 things is: getting an inheritance with a voter turnout of 78 respondents or 52%. The second position wants to be independent with 50 respondents or 33%. The third position is close to the workplace with a voter turnout of 20 respondents or 13%.